Climate change and grasslands: impacts, adaptation and mitigation - Hopkins A. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The paper reviews recent evidence on climate change and the role of greenhouse gases (GHG). Historical evidence indicates that climate change is not a new phenomenon and Mediterranean ecosystems have shown considerable resilience to past climate changes. The 21st century can be regarded as an era of climate change in which concerns about climate are accompanied by other drivers relating to globalization, food security and energy and sustainability issues. Carbon dioxide enhancement can have positive and negative effects for forage production. Increased temperatures and water deficits in the Mediterranean zone are likely to impact adversely on production, based on modelled outcomes, especially on maximum-production systems, but climate-adapted and regionally diverse systems of agriculture are suggested as being more resilient to climate change impacts. A range of adaptation strategies at both farm level and at policy/ government level are considered as means of enabling grass and forage systems to be maintained in a changing climate. Livestock agriculture contributes to GHG emissions but a range of mitigation measures are considered that can help offset some of these emissions. It is concluded that an integrated approach is required to respond to climate change. Many challenges remain but there are grounds for cautious optimism for future grass and forage-based farming in the Mediterranean zone.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)